KADAR AFLATOXIN DALAM KACANG TANAH DAN HASIL OLAHANNYA - Muhilal Muhilal; Darwin karyadi; Dradjat D. Prawiranegara (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 1971)
Kadar aflatoxin dalam katjang tanah dan hasil olahnja (The aflatoxin contents of peanut and peanut products). Gizi Indonesia, 2: 162, 1970. Samples of peanut and peanut products obtained in Bogor were analyzed for their contents of aflatoxin by the method of Pons and Goldblatt. The peanut products analyzed were peanut oil, peanut presscake, peanut butter and fermented peanut presscake. Most of the aflatoxin found was of Bl type which is the most toxic. The aflatoxin contents of peanut bought from retailers (40 to 4100 ppb) were roughly 25 times the safe level designated by the American and Canadian Food and Drug Administration. It was noticel that the longer the time needed for peanuts to reach the consumer, the greater are the contents of aflatoxin. Kacang tanah merupakan bagian dari menu orang Indonesia. Ada berbagai bahan makanan yang memakai kacang tanah/hasil olahan kacang tanah sebagai bahan dasarnya, yang paling terkenal ialah oncom yang banyak terdapat di Jawa Barat. Mengingat kemungkinan bahaya yang bisa ditimbulkan aflatoxin, maka penelitian kadar aflatoxin pada kacang tanah dan hasil olahannya sangat penting terutama dari segi kesehatan masyarakat.